RECYCLING OF PINEAPPLE WASTE USING LACTOBACILLUS DELBROECKII TO LACTIC ACID - Moch Busairi, Abdullah (Gema Teknologi, 2010)
Abdullah, in paper recycling of pineapple waste using lactobacillus delbroeckii to lactic acid, explain that The pineapple wastes juice contains mainly sucrose, glucose, fructose and other nutrients. It therefore can potentially be used as carbon source for organic acid fermentation. Recently, lactic acid has been considered to be an important raw material for production of biodegradable lactate polymer. The experiments were carried out in shake flask fermentation using Lactobacillus delbrueckii. Effect of some parameters such as temperature, initial pH, initial substrate concentration, yeast extract concentration and fermentation time to the yield have been studied. The highest yield was 85.65 % achieved at 40 o C, pH 6.00, 52.5 g/l sugar concentration with 5 g/l yeast extract. There was no significant increasing in lactic acid production was observed if supplementation of yeast extract above 10 %..